1996
DOI: 10.1142/s0217732396003064
|View full text |Cite
|
Sign up to set email alerts
|

Parastatistics as Examples of the Extended Haldane Statistics

Abstract: We show that for every algebra of creation and annihilation operators with a Fock-like representation, one can define extended Haldane statistical parameters in a unique way. In particular for parastatistics, we calculate extended Haldane parameters and discuss the corresponding partition functions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Similar approach has been also considered by others authors, see [35,36,37] and [38,39]. An interesting approach to quantum statistics has been also given in [40,41]. A proposal for the general algebraic formalism for description of particle systems equipped with an arbitrary generalized statistics based on the concept of monoidal categories with duality has been given by the author in [42].…”
Section: Introductionmentioning
confidence: 85%
“…Similar approach has been also considered by others authors, see [35,36,37] and [38,39]. An interesting approach to quantum statistics has been also given in [40,41]. A proposal for the general algebraic formalism for description of particle systems equipped with an arbitrary generalized statistics based on the concept of monoidal categories with duality has been given by the author in [42].…”
Section: Introductionmentioning
confidence: 85%
“…In a previous paper [16] we found that any operator algebra of creation and annihilation operators with a Fock-like representations could be described in terms of extended Haldane statistics parameters. Using this result, we described para-Fermi and para-Bose statistics as exclusion statistics of the Haldane type and calculated a few extended statistics parameters.…”
Section: Introductionmentioning
confidence: 94%
“…In this section we briefly review the definition of general multimode oscilator algebras possessing Fock-like representations and well defined number operators [16,17].…”
Section: Definition Of the Multimode Oscillator Algebras 21 Fock Spacementioning
confidence: 99%
See 1 more Smart Citation
“…We discuss them in the framework of the Haldane's definition of statistics 9 . We point out that none of them is an example of the original Haldane exclusion statistics, but can be related to the so-called extended Haldane statistics 10 . For each of them we find the extended Haldane statistics parameters .…”
Section: Introductionmentioning
confidence: 99%